ANALISIS KALIBRASI SUHU PADA INFANT WARMER MENGGUNAKAN METODE ECRI 415-200010301-01 - Iwan Ara Rizki; Hotromasari Dabukke (JURNAL MUTIARA ELEKTROMEDIK, 2019)
Infant warmer is an electromedic device which is used to provide comfort and warmth in a newborn, where the baby needs a temperature that is in accordance with the temperature in the mother’s womb,which is between 34 C - 37 C. Infant warmer calibration activities refer to the ECRI method 415-20010301. As the treshold value or the value of passing the test is +- 2 C for temperature. The results obtained from calibration are 31,89+- 0,51 C for temperature. From these results it was stated that the GIGANTE infant warmer was declared to be suitable for use.